2012
DOI: 10.1210/en.2011-1638
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate Treatment Protects Blood-Brain Barrier Pericytes from Hyperglycemia-Induced Oxidative Damage in Diabetic Mice

Abstract: Diabetes mellitus causes cerebral microvasculature deterioration and cognitive decline. The specialized endothelial cells of cerebral microvasculature comprise the blood-brain barrier, and the pericytes (PC) that are in immediate contact with these endothelial cells are vital for blood-brain barrier integrity. In diabetes, increased mitochondrial oxidative stress is implicated as a mechanism for hyperglycemia-induced PC loss as a prerequisite leading to blood-brain barrier disruption. Mitochondrial carbonic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
112
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(126 citation statements)
references
References 59 publications
9
112
0
1
Order By: Relevance
“…A possible mechanism responsible for the prevention of mitochondrial depolarization and H 2 O 2 production is that pharmacological inhibition of mitochondrial CAs slows down the production of HCO3, limiting Krebs cycle and electron transport chain, and thus reducing the production of H 2 O 2 and subsequent oxidative stress. This mechanism is also proposed by Shah's group, who showed that inhibition of CAs rescued high‐glucose induced mitochondrial dysfunction, ROS production, and pericyte loss in diabetic mice (Price, Eranki, Banks, Ercal & Shah, 2012; Shah, Morofuji, Banks & Price, 2013). The known effects of CAIs on specific ion channels, aquaporins (Kamegawa, Hiroaki, Tani & Fujiyoshi, 2016), or other receptors which interact with Aβ on mitochondrial or cell membranes may also be mechanisms responsible for the amelioration of Aβ‐induced mitochondrial dysfunction (Aggarwal et al., 2013).…”
Section: Discussionsupporting
confidence: 54%
“…A possible mechanism responsible for the prevention of mitochondrial depolarization and H 2 O 2 production is that pharmacological inhibition of mitochondrial CAs slows down the production of HCO3, limiting Krebs cycle and electron transport chain, and thus reducing the production of H 2 O 2 and subsequent oxidative stress. This mechanism is also proposed by Shah's group, who showed that inhibition of CAs rescued high‐glucose induced mitochondrial dysfunction, ROS production, and pericyte loss in diabetic mice (Price, Eranki, Banks, Ercal & Shah, 2012; Shah, Morofuji, Banks & Price, 2013). The known effects of CAIs on specific ion channels, aquaporins (Kamegawa, Hiroaki, Tani & Fujiyoshi, 2016), or other receptors which interact with Aβ on mitochondrial or cell membranes may also be mechanisms responsible for the amelioration of Aβ‐induced mitochondrial dysfunction (Aggarwal et al., 2013).…”
Section: Discussionsupporting
confidence: 54%
“…228 One factor contributing to BBB disruption is pericyte loss 229 that occurs from hyperglycemia-induced mitochondrial oxidative stress in a rodent model of diabetes. 149 Pericyte loss in this model is blocked by the carbonic anhydrase inhibitor topiramate that shifts glucose metabolism to aerobic glycolysis and prevents generation of superoxide. 149 Together, these results suggest that diabetes causes BBB dysfunction that could contribute to AD.…”
Section: Alzheimer's Disease Risk Factors and The Blood-brain Barriermentioning
confidence: 99%
“…149 Pericyte loss in this model is blocked by the carbonic anhydrase inhibitor topiramate that shifts glucose metabolism to aerobic glycolysis and prevents generation of superoxide. 149 Together, these results suggest that diabetes causes BBB dysfunction that could contribute to AD. Traumatic Brain Injury Traumatic brain injury (TBI) increases the risk for developing AD by 2-to 4.5-fold, depending on severity of the injury.…”
Section: Alzheimer's Disease Risk Factors and The Blood-brain Barriermentioning
confidence: 99%
“…DM rats suffer from vascular damage, which is aggravated after an ischemic insult; the effects of VEGF may be exacerbated in DM stroke rats compared with nondiabetic stroke rats 42, 43. In DM, mitochondrial oxidative stress leads to both endothelial cell damage as well as pericyte depletion and BBB leakage 44. In the minutes to hours following ischemia, endothelial swelling and pericytes mediate capillary constriction, which is followed by rapid pericyte death leading to irreversible constriction of capillaries and BBB damage 34, 45…”
Section: Blood–brain Barrier Disruption In Diabetic Strokementioning
confidence: 99%
“…Mitochondrial oxidative stress with an increased abundance of reactive oxygen species (ROS) after I/R is a key mediator of diabetic, stroke, and diabetic stroke pathologies 44. ROS generated from mitochondria mediate neurodegeneration and apoptotic signaling pathways after stroke.…”
Section: Mechanisms Of Ischemia/reperfusion Damage In Diabetic Strokementioning
confidence: 99%